ANALYSIS OF WEIGHT FALTERING INCIDENTS IN TODDLERS IN THE WORK AREA OF TANJUNG RAMBANG HEALTH CENTER, PRABUMULIH CITY - Siti Anisa Maulidia; Akhmad Dwi Priyatno; Chairil Zaman; Edy Sapada; Lisa Fitri (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
The maximum development potential of children under five is strongly influenced by nutrition. Estimates of stunting, wasting, overweight, and underweight as markers of child malnutrition. The most dominant stunting that occurs in toddlers is the problem of growth failure or weight faltering. Methods Research using cross-sectional. Population consists of mothers who have toddlers, who visit posyandu ILP Mekar Jaya in Talang Batu Village in February 2025 using purposive sampling technique obtained 53 respondents. The results of the study obtained age of toddlers p value = 0.04 OR 0.32, gender pvalue 0.90, birth weight pvalue 0.29, exclusive breastfeeding p value = 0.02 OR 0.27, maternal age p value =0.48, maternal education p value =0.16, parental income p value = 0.95, maternal knowledge p value Value =0.01 OR 4.25. From the final results of multivariate analysis. Variable knowledge with p value = 0.017 OR 4.250. Conclusion there is a significant relationship between the age of toddlers, exclusive breastfeeding and maternal knowledge of the incidence of weight falterin. The more dominant variableis knowledge